The Influence Of Digital Work Culture, Team Collaboration And Psychological Capital Of Teaching Staff On Organizational Agility In Higher Education Institutions - Almira Ulimaz; Sri Purwati; Akhmad Ramli; Agus Rofi'i; Desi Aryani; Apriani Riyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Educational institutions need to establish operational adaptability through their educational space transformations which occur on a continuous basis. The research investigates how digital work culture and team collaboration together with faculty members' psychological capital impact higher education institutions' ability to achieve organizational agility. The researchers employed quantitative research methods together with an explanatory research framework as their study approach. The research collected data through a survey which used a structured questionnaire to gather information from 180 faculty members who worked at various Indonesian higher education institutions. The researchers performed data analysis through multiple linear regression after establishing both validity and reliability together with the classical assumption tests. The research demonstrates that digital work culture and team collaboration together with faculty members' psychological capital create a positive impact which leads to improved organizational agility. The research finding shows that academic institutions develop their organizational agility through three elements which include cultural elements social elements and psychological factors. The strategic results show higher education leaders the way to develop organizational development policies which enable their institutions to become adaptive while creating sustainable progress.